2009
DOI: 10.17660/actahortic.2009.847.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (Changes In) Air Humidity on Transpiration and (Adaptation Of) Stomatal Closure of Tradescantia Leaves During Water Stress

Abstract: This paper summarises our recent research on the physiological effects of prolonged high RH during growth on stomatal function and we discuss possibilities that arise from this work for reducing postharvest quality problems in cut flowers. Chlorophyll fluorescence imaging was used to measure stomatal closure in response to desiccation of Tradescantia virginiana leaves grown under high (90%) and moderate (55%) relative humidities, or transferred between these humidities. Stomata of plants transferred from moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…If subjected to a prolonged exposure to a low VPD, however, a habituation process occurs which renders the stomata insensitive to stimuli that would otherwise provoke stomatal closure. Stimuli shown to become ineffective in this way include desiccation (Rezaei Nejad and van Meeteren, 2005; Rezaei Nejad et al , 2006; van Meeteren et al , 2009), high VPD (Torre et al , 2003; Rezaei Nejad and van Meeteren, 2008; Mortensen and Gislerød, 2011), darkness (Mortensen and Fjeld, 1998; Fanourakis et al , 2013 a ), abscisic acid (ABA) (Ziv et al , 1987; Rezaei Nejad and van Meeteren, 2005, 2007), and the nitric oxide (NO) donor sodium nitroprusside (SNP) (Rezaei Nejad and van Meeteren, 2007). Similar to stomata of Tradescantia virginiana plants grown at low VPD, the loss of stomatal functioning took place 4 d after transfer of fully grown leaves (grown at moderate VPD) to low VPD conditions (Rezaei Nejad and van Meeteren, 2008).…”
Section: Role Of Duration Of Exposure To Environmental Factors In Stomentioning
confidence: 99%
“…If subjected to a prolonged exposure to a low VPD, however, a habituation process occurs which renders the stomata insensitive to stimuli that would otherwise provoke stomatal closure. Stimuli shown to become ineffective in this way include desiccation (Rezaei Nejad and van Meeteren, 2005; Rezaei Nejad et al , 2006; van Meeteren et al , 2009), high VPD (Torre et al , 2003; Rezaei Nejad and van Meeteren, 2008; Mortensen and Gislerød, 2011), darkness (Mortensen and Fjeld, 1998; Fanourakis et al , 2013 a ), abscisic acid (ABA) (Ziv et al , 1987; Rezaei Nejad and van Meeteren, 2005, 2007), and the nitric oxide (NO) donor sodium nitroprusside (SNP) (Rezaei Nejad and van Meeteren, 2007). Similar to stomata of Tradescantia virginiana plants grown at low VPD, the loss of stomatal functioning took place 4 d after transfer of fully grown leaves (grown at moderate VPD) to low VPD conditions (Rezaei Nejad and van Meeteren, 2008).…”
Section: Role Of Duration Of Exposure To Environmental Factors In Stomentioning
confidence: 99%
“…Photosynthesis rate of plants under drought stress is decreased [9]. In this study, we found that the Pn, Tr, Gs and photochemical efficiency (ФPSⅡ) decreased with the increasing degree of stress, because the decrease of LRWC would lead to stomatal closure and decrease of stomatal conductance [10]. While Ci showed an upward trend.…”
Section: Discussionmentioning
confidence: 72%
“…In other studies, increasing the VPD during a critical stage of stomatal development resulted in a normal closing response of stomata (Ghashghaie et al, 1992;Fanourakis et al, 2011;Maleki Asayesh et al, 2017a). It is also likely that short interruptions of the low VPD every few (about 3) days by high VPD will prevent induction of stomatal malfunction (van Meeteren et al, 2009).…”
Section: How To Prevent Stomatal Malfunctionmentioning
confidence: 86%